2019
DOI: 10.20960/nh.02590
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Lupinus mutabilis Sweet snack as complement to conventional type 2 diabetes mellitus treatment

Abstract: AC, Guzmán Aburto MB. Efectos del té verde y su contenido de galato de epigalocatequina (EGCG) sobre el peso corporal y la masa grasa en humanos. Una revisión sistemática. Nutr Hosp 2017;34:731-737 DOI: http://dx.doi.org/10. 20960/nh.753 Efectos del té verde y su contenido de galato de epigalocatequina (EGCG) sobre el peso corporal y la masa grasa en humanos. Una revisión sistemática Effects of green tea and its epigallocatechin (EGCG) content on body weight and fat mass in humans: a systematic reviewResume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The prospective urban rural epidemiology (PURE) study has shown in 18 low-middle income countries, not including Ecuador, that high consumption of legumes (3 to 4 servings/day) is associated with a 22% decrease in total-and non-cardiovascular mortality risks [10]. Our group has also shown that consumption of Lupinus mutabillis, an Andean legume commonly consumed in Ecuador, improves metabolic control in individuals with T2D, reducing serum concentrations of glycated hemoglobin and decreasing blood pressure [11]. In vitro studies show that L. mutabilis hypoglycemic effects could be attributed to the enzymatic inhibition of dipeptidyl peptidase-IV, inhibition of hepatic gluconeogenesis, and decreased insulin resistance [12].…”
Section: Introductionmentioning
confidence: 73%
“…The prospective urban rural epidemiology (PURE) study has shown in 18 low-middle income countries, not including Ecuador, that high consumption of legumes (3 to 4 servings/day) is associated with a 22% decrease in total-and non-cardiovascular mortality risks [10]. Our group has also shown that consumption of Lupinus mutabillis, an Andean legume commonly consumed in Ecuador, improves metabolic control in individuals with T2D, reducing serum concentrations of glycated hemoglobin and decreasing blood pressure [11]. In vitro studies show that L. mutabilis hypoglycemic effects could be attributed to the enzymatic inhibition of dipeptidyl peptidase-IV, inhibition of hepatic gluconeogenesis, and decreased insulin resistance [12].…”
Section: Introductionmentioning
confidence: 73%